Estradiol Ameliorates Acute Kidney Ischemia-Reperfusion Injury by Inhibiting the TGF-βRI-SMAD Pathway - Ren, Lian; Li, Fang; Di, Ziyang; Xiong, Yan; Zhang, Shichen; Ma, Qing; Bian, Xiaoen; Lang, Zhiquan; Ye, Qifa; Wang, Yanfeng (Frontiers in Immunology, 2022)
Females of both animals and humans suffer renal ischemia-reperfusion injury (IRI) to a lesser extent relative to the males, however, this protection diminishes after menopause, suggesting that estrogen may play a pivotal role in IRI, wherein, the underlying mechanism remains largely unknown. Our study found that 45 min of warm ischemia was sufficient to induce significant pathological changes without causing death in model animals. Compared to the male rats, female rats exhibited lesser apoptosis, kidney injury and fibrosis; these effects were worsened in ovariectomized (OVX) rats and ameliorated upon estradiol (E2) supplementation. Furthermore, TGF-βRI, but not TGF-βRII or TGF-β1 levels, was significantly enhanced in OVX rats, followed by phosphorylated SMAD2/3 activation. Interestingly, the alteration in nuclear ERα levels showed opposite trends relative to those of TGF-βRI. Furthermore, the dual-luciferase reporter and chromatin immunoprecipitation assays showed that ERα could bind to the promoter region of TGF-βRI and negatively regulate its mRNA expression. Moreover, an in vitro study using NRK-52E cells showed that ERα knockdown could block E2-mediated protection, while TGF-βRI knockdown protected cells against hypoxic insult. The findings of this study suggested that the renal IRI was closely related to the TGF-βRI-SMAD pathway in the females, and E2 could exert its protection through the ERα-mediated transcriptional inhibition of TGF-βRI’s expression.